Touch - Field, Tiffany (Bradford Bks., 2001)
An essay on the importance of touch to children's growth and development and to the physical and mental well-being of people of all ages. The first sensory input in life comes from the sense of touch while a baby is still in the womb, and touch continues to be the primary means of learning about the world throughout infancy, well into childhood. Touch is critical for children's growth, development, and health, as well as for adults' physical and mental well-being. Yet American society, claims Tiffany Field, is dangerously touch-deprived. Field, a leading authority on touch and touch therapy, begins this accessible book with an overview of the sociology and anthropology of touching and the basic psychophysical properties of touch. She then reports recent research results on the value of touch therapies, such as massage therapy, for various conditions, including asthma, cancer, autism, and eating disorders. She emphasizes the need for a change in societal attitudes toward touching, particularly among those who work with children.